MANUFACTURING AND CHARACTERIZATION OF SUGAR BEET PULP PARTICLES FILLED POLYPROPYLENE MATRIX BIOCOMPOSITE - Gökdemir, Barış; Sever, Kutlay; Atagür, Metehan; Şen, İbrahim (My University, 2025)
In this study, Polypropylene (PP) matrix biocomposites were developed with the aim of reducing sugar beet pulp (SP) waste and demonstrating the potential of agricultural waste materials in various applications. Sugar beet pulp extracted from a sugar production factory was subjected to a drying process and then mechanically ground. Following this process, the resultant powdered sugar beet pulp particles were subjected to a sieving process, yielding particles within the size range of 100–250 ?m. These particles were then incorporated into the pure PP matrix at filling levels ranging from 5% to 20%. Subsequently, the mechanical (tensile, flexural, DMA), thermal (TGA, DSC), and chemical (FTIR) properties of these biocomposites were investigated. DMA results indicated a notable improvement in storage modulus with increased filler content, supporting the stiffening effect of sugar beet pulp particles. DSC analysis showed minimal change in melting temperature, but a slight decrease in crystallinity degree with higher filler ratios. FTIR spectra confirmed the presence of characteristic functional groups from lignocellulosic sugar beet pulp within the PP matrix, indicating successful incorporation. It was determined that the elastic modulus in the PP matrix biocomposites increased as the amount of sugar beet pulp particles increased. When the thermogravimetric analysis (TGA) data of PP and biocomposites were compared, an increase in the maximum degradation temperature (Tmax) was observed as the SP100 and SP250 ratio increased, while a decrease in the temperature at which degradation began (Ton) was observed. These biocomposites demonstrate promising potential for application in the automotive, packaging, and construction industries as sustainable materials.
Keywords: Characterization; Biocomposite; Polypropylene (PP); Mechanic and thermal properties.; Sugar beet pulp waste